Systemic Agility and Job Strain: A Mediation Model - Bronlet, Xavier; Canzani, Chiara (Archives of Business Research, 2024)
While turbulent environments and crises have an impact on Job Strain and create stress within the companies, there are many approaches about how to adapt and thrive in an increasingly turbulent operating environment, however the extant literature on the subject is mainly qualitative. The case study examines the impact of VUCAness, defined as the level of turbulence in the operating environment (independent variable) on Job Strain (dependent variable), mediated by the Systemic Agility (mediating variable), defined as the level of cultural agility. The mediation variable is assessed using the significant domains that emerge from our review of the literature and quantifies the positioning of the observed organisations on a continuum between legacy and agile culture, between modern and postmodern perspectives. Job strain is measured by Karasek’s established Job Content Questionnaire. The case study illustrates the partial mediation effect of the Systemic Agility, on Job Strain using 307 observations collected in a company group made of two distinct groups. The study confirms the partial mediation effect of Systemic Agility on Job Strain and suggests that, above a certain level of agility, the mediation effect turns from negative to positive, reducing the stress induced by the operating environment. This quantitative case study suggests that the agile culture mediates stress at the workplace under turbulent working conditions.